Managing and Supporting Surgery in Patients with Bleeding Disorders - Curnow, Jennifer (Seminars in Thrombosis and Hemostasis, 2017)
Patients with inherited bleeding disorders are likely to require surgery at various times throughout life. In some cases, this may be major orthopaedic surgery required due to their underlying condition, for example, hemophilic arthropathy. For inherited disorders with significant bleeding risk, surgery should take place in a hemophilia treatment center with the availability of hematologic, anesthetic, surgical, nursing, scientific laboratory, and allied health expertise. Preoperative assessment, planning, and communication between team members are crucial. Specific replacement therapy is usually required, as may other adjunctive therapies. Venous thromboembolism (VTE) risk assessment is individualized, taking account of other underlying risks in the patient and risks associated with the procedure, including the replacement agent itself, and use of mechanical prophylaxis may be the safest approach in many cases. Pain management is also modified to take account of risks associated with the bleeding disorder, and spinal or epidural analgesia is restricted compared with patients who do not have hemostatic defects. In patients with acquired bleeding disorders, the preoperative assessment includes decisions regarding how best to optimize management of the underlying condition prior to proceeding with surgery. If this is achieved, specific replacement therapy may not be required. If complete remission of the acquired bleeding disorder is achieved preoperatively, then VTE prophylaxis and pain management options will not be limited by the bleeding disorder. The perioperative management of both hereditary and acquired bleeding disorders is discussed and contrasted.
Keywords: inherited bleeding disorders; acquired bleeding disorders; perioperative management; factor concentrates; thromboprophylaxis